Copper-induced cell death mechanisms and their role in the tumor microenvironment - Jiao, Yujuan; Wang, Hongxin; Zhu, Meng; Liu, Tengteng; Li, Yuqi; Yang, Shuo; Zhang, Minghui; Zhang, Lei (Frontiers in Cell Death, 2025)
Copper is an essential cofactor for all organisms. However, it can become toxic if its concentration rises above a specific level. This level is controlled by evolutionary conserved homeostatic mechanisms. Recently, a new type of cell death called cuproptosis has been found. The process represents a copper-dependent, regulated form of cell death that is distinct from all known death mechanisms and relies on mitochondrial respiration. The mechanism of cuproptosis involves the direct binding of copper to lipidated parts in the tricarboxylic acid (TCA) cycle. This results in the abnormal aggregation of lipoylated proteins and the destabilization of iron-sulfur cluster (Fe-S) proteins. These events induce proteotoxic stress, ultimately leading to cell death. Copper-induced cell death is controlled by proteolipid acylation, which is mediated by the mitochondrial iron-sulfur protein FDX1. Copper overload also inhibits the biosynthesis of iron-sulfur (Fe-S) clusters and impairs the activity of Fe-S enzymes. As a result, mitochondrial function is disrupted. Both copper-induced cell death and impaired copper homeostasis arise from the same mechanistic basis. The expression of copper import gene SLC31A1 (CTR1) and export genes ATP7A and ATP7B significantly influences cuproptosis. The tumor suppressor p53 may participate in this process by modulating glycolysis and mitochondrial metabolism. In contrast, glutathione (GSH) reduces copper ion cytotoxicity by binding copper to form a complex. The growth and spread of tumor cells is more dependent on copper than that of normal cells.The copper ionophore elesclomol (ES) kills cancer cells by transporting copper ions into them. This ES-Cu complex not only inhibits cancer cell proliferation but also activates an immune response. Moreover, when ES is combined with αPD-L1, it might increase the effectiveness of cancer treatment. This gives a new idea for treating cancer.